2011
DOI: 10.1016/j.trsl.2011.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus, a microRNA-related disease?

Abstract: Diabetes mellitus is a complex disease resulting in altered glucose homeostasis. In both type 1 and type 2 diabetes mellitus, pancreatic β cells cannot secrete appropriate amounts of insulin to regulate blood glucose level. Moreover, in type 2 diabetes mellitus, altered insulin secretion is combined with a resistance of insulin-target tissues, mainly liver, adipose tissue, and skeletal muscle. Both environmental and genetic factors are known to contribute to the development of the disease. Growing evidence ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
211
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 273 publications
(221 citation statements)
references
References 76 publications
1
211
0
5
Order By: Relevance
“…Upregulation and downregulation of miRNAs are strongly associated with T1D and T2D. miRNAs directly target genes involved in b-cell survival and insulin exocytosis, and insulin resistance is the central mechanism of miRNAs-mediated T1D and T2D (FernandezValverde et al 2011, Guay et al 2011, Rottiers & Naar 2012, Samuel & Shulman 2012, Williams & Mitchell 2012. Manipulation of miRNAs and insulin signaling may have therapeutic potential.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Upregulation and downregulation of miRNAs are strongly associated with T1D and T2D. miRNAs directly target genes involved in b-cell survival and insulin exocytosis, and insulin resistance is the central mechanism of miRNAs-mediated T1D and T2D (FernandezValverde et al 2011, Guay et al 2011, Rottiers & Naar 2012, Samuel & Shulman 2012, Williams & Mitchell 2012. Manipulation of miRNAs and insulin signaling may have therapeutic potential.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…Overall, these and many other studies (reviewed extensively elsewhere [1][2][3]) have identified microRNAs as essential players in beta cell development and function and in the regulation of whole body glucose homeostasis.…”
Section: Micrornas As Regulators Of Beta Cell Differentiation and Funmentioning
confidence: 87%
“…A growing number of studies demonstrate that these changes are not only caused by deregulation of key transcription factors such as v-maf musculoaponeurotic fibrosarcoma oncogene family, protein A (avian) (MafA) or pancreatic and duodenal homeobox 1 (PDX1) but are also driven by modifications in the level of another group of molecules regulating gene expression, the microRNAs [1][2][3][4]. MicroRNAs are small non-coding RNAs (typically 21-23 nucleotides long) that pair to the 3′ untranslated region of target mRNAs leading to translational repression and/or a decrease in messenger stability [5].…”
Section: Micrornas As Regulators Of Beta Cell Differentiation and Funmentioning
confidence: 99%
“…Prolonged exposure to cytokines leads to a decreased capacity of b cells to produce and release insulin in response to secretagogues and, in the long term, destruction of the cells by apoptosis or necrosis. 25,28 T1D typically affects young children, with onset as early as 1 year of age; most cases are diagnosed before the patient is 18 years old. The autoimmune process starts even earlier, as evidenced by the presence of autoantibodies in serum against T1D-specific antigens.…”
Section: Multifactorial Etiology Of T1dmentioning
confidence: 99%
“…87 In light of these results, measurement of specific miRNA levels may be useful for identifying people at risk for developing T1D, possibly preventing the development of the disease. 28 Lentiviral transgenesis has been used to generate NOD mice in which the Slc11a1 T1D candidate gene was silenced by RNA interference. Silencing reduced the frequency of T1D, thus demonstrating a role for Slc11a1 in modifying susceptibility to T1D.…”
mentioning
confidence: 99%